Strategies and technologies for enhancing rapeseed-mustard production and farmer income - Sharma, Pankaj; Sharma, Hari Om; Rai, P. K. (Indian Farming, 2018)
As policy measures to attract the farmers towards oilseeds, in general, and rapeseed-mustard in particularly, favourable support price, higher tariff rate on import of edible oil and effective market intervention would have to be looked. Bee-keeping in rapeseed-mustard crop can increase the yield by 15 to 20% and will generate additional income to farmers. Conduction of more number of on different production and protection aspects for effective dissemination of technology is needed.